Studies on Black Iron Oxide Pigment. Part-II: Effect of Preparation Parameter on Particle Size and Microstructure of Ferrosoferric Oxide - Neger, AJM Tahuran; Ahmed, Aftabuddin; Parvin, Sufia; Alam, AM Shafiqul (Bangladesh Journal of Scientific and Industrial Research, 2009)
This paper deals with the effect of preparation parameter on particle size and microstructure of the prepared ferrosoferric oxide. 10 prepared samples (from 23 samples) and one standard sample (Bayferrox 318 standard 88) collected from BAYER, Germany was selected for this study. X-ray diffraction, petrographic microscopy, scanning electron microscope and particle size analyzer were used to characterize the phase present, particle size and shape of the particle. It is observed from X-ray diffraction that all these samples mainly contain Fe3O4 phase. The shape of the particle is found to be round and agglomerated. The average particle diameter of highest portion of pigment in the peak region is ranged from 12.25μ to 17.32μ, which is very similar to the standard sample (17.32μ). Sample number 9, which was prepared with ferrous sulphate, hydrochloric acid, sodium nitrate and ammonium hydroxide at a molar ratio 1:1.74:0.16:4.07 and standard sample contain narrow high peak in their particle size distribution curve. Another observation is that, experimental parameter, though have some effect on particle size but have no effect on microstructure. Key words: Black iron oxide, Pigment, Particle size, Microstructure, Ferrosoferric oxide. doi: 10.3329/bjsir.v44i1.2711 Bangladesh J. Sci. Ind. Res. 44(1), 31-40, 2009